Mapping two new points on the tennis expertise continuum: Tactical skills of adult advanced beginners and entry-level professionals during competition - McPherson, S. L.; Kernodle, M. (Journal of Sports Sciences, 2007)
Research examining problem representations of individuals during task performance is advancing our understanding of information processing and expertise in a variety of sports. However, few studies using similar methodology have been conducted on individuals of various competitive standards in one domain in similar contexts. This study examined problem representations of adult advanced beginners and entry-level professionals accessed during singles tennis competition (n = 12). These groups were selected to represent players with performance skills that were different from those studied previously (i.e. adult beginners and varsity players). Immediate recall and planning interviews were conducted between points during singles tennis competition. Players competed within their respective expertise groups. Verbal reports were transcribed verbatim and concepts were scored according to a model of protocol structure. Several multivariate analyses of variance were conducted on rank scores for measures of concept content and structure using the L-statistic. Entry-level professionals exhibited more advanced problem representations than advanced beginners regardless of interview type. These findings together with those of previous research suggest adaptations in long-term memory profiles with increases in performance skills. For example, beginners lacked action plan and current event profiles because they generated goals and reiterated game events during both interviews. Advanced beginners, who had better performance skills than beginners, exhibited rudimentary action plan profiles and deficient current event profiles because they generated and monitored several detailed actions related to the current context during recall interviews and generated only a few goals during planning interviews. In contrast, varsity players and professionals processed tactical information in the current context and beyond denoting the existence of both action plan and current event profiles. Varsity players, with inferior performance skills than professionals, exhibited fewer and less associated tactical concepts than professionals during both interviews.